Ethics : a very short introduction - Blackburn, Simon, 1944- (Very short introductions - paper, 2021)
"Ethics: A Very Short Introduction highlights the importance of an understanding of approaches to ethics and its foundations. Today, we are confronted with an uncertain world of eroding trust, swirling conspiracy theories, and a dismaying loss of respect in public discourse. Our self-image as moral, well-behaved creatures is dogged by scepticism, relativism, hypocrisy, and nihilism, and by the fear that science has unmasked us as creatures fated by our genes to be selfish, competitive, and aggressive. This VSI tackles the major moral questions surrounding birth, death, happiness, desire, and freedom. It shows us how we should think about the meaning of life"--